Anatomy of Mahakala omnogovae (Theropoda: Dromaeosauridae), Tögrögiin Shiree, Mongolia - Turner, Alan Hamilton (2011)
The dromaeosaurid Mahakala omnogovae is known from a unique specimen from the late Cretaceous deposits of the Djadokhta Formation at Tögrögiin Shiree, Ömnögov Aimag, Mongolia. The holotype specimen is comprised of a well-preserved but partial skull and a nearly complete postcranial skeleton. Mahakala omnogovae is included in a comprehensive phylogenetic analysis of Coelurosauria using a dataset, which reflects a greatly expanded character set and taxon-sampling regime. Several interesting features of Mahakala omnogovae have implications for deinonychosaurian and avialan character evolution and for understanding patterns of size variation and size change within paravian theropods. These morphologies include the shape of the iliac blade, the triangular obturator process of the ischium, and the evolution of the subarctometatarsalian condition. We present an expanded diagnosis of Mahakala omnogovae which included following unique combination of characters (autapomorphies noted by *): a ledgelike depression at the confluence of metotic strut and posterior tympanic recess on the anterior face of the paroccipital process*, a posteriorly tapering scapula; a shortened forelimb (humerus 50% femur length); a strongly compressed and anteroposteriorly broad ulna tapering posteriorly to a narrow edge*; elongate lateral crest on the posterodistal femur*; anterior caudal vertebrae with subhorizontal, laterally directed prezygapophyses*; a prominent supratrochanteric process; and the absence of a cuppedicus fossa.